2021
DOI: 10.26832/24566632.2021.060104
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of dietary protein level for good aquaculture practice based carp fattening in ponds under drought prone area of Bangladesh

Abstract: Good aquaculture practice (GAP) based carp fattening is a potential technique to obtain higher and safe fish production within shorter period in ponds of drought prone area. Sustainability of this technique, however, is constrained by high feed cost and poor water quality. Therefore, as an overcoming effort, three diets (protein content of 20%, 25% and 30%) under three different treatments (T1, T2 and T3) were tested during January-June, 2020 in fattening ponds of carps (Catla, Gibelion catla; silver carp, Hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Study shows that the partial replacement of FM by PPI can reduce Phosphorous (Ketola and Harland, 1993) and Nitrogen excretion (as ammonia) by reducing protein levels (Cheng et al, 2003). Therefore, additional research is needed to adequately determine the inclusion rate of PPI in the partial replacement of FM in fish diet which could be readily available, cheap and environmentally friendly (Hernández et al, 2016;Hossain et al, 2021). Studies indicate that diets allowing for the partial or complete substitution of FM can be feasible through a meticulous formulation process (Espe et al, 2006;Kousoulaki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Study shows that the partial replacement of FM by PPI can reduce Phosphorous (Ketola and Harland, 1993) and Nitrogen excretion (as ammonia) by reducing protein levels (Cheng et al, 2003). Therefore, additional research is needed to adequately determine the inclusion rate of PPI in the partial replacement of FM in fish diet which could be readily available, cheap and environmentally friendly (Hernández et al, 2016;Hossain et al, 2021). Studies indicate that diets allowing for the partial or complete substitution of FM can be feasible through a meticulous formulation process (Espe et al, 2006;Kousoulaki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Gandotra et al (2015) and Obirikorang et al (2015) also reported that feed constitute 40-70% of the variable cost in aquaculture production. Therefore, quality feed production is a major challenge for small farmmade feed producers and commercial feed millers (Hossain et al, 2021;Bhuyain et al, 2019). In this context, the utilisation of nanoparticles containing trace elements holds potential for promoting the growth and development of fish.…”
Section: Introductionmentioning
confidence: 99%